Multisensory Facial Stimulation Implicitly Improves Evaluations of the Goodness of Attractive Others - Jeong, Ji Woon; Chang, Eunhee; Kim, Hyun Taek (Frontiers in Psychology, 2019)
It has been well demonstrated that shared multisensory experiences between the self and others can influence the social perception of outgroup members. Previous research has shown that the illusion of ownership over a dark-skinned rubber hand or full virtual body generated less negative implicit bias against people with dark skin. However, less is known about how perceived attractiveness difference between self and other affects social perception toward those others after share multisensory experience. The present study assessed whether shared multisensory experience between the self and attractive others would affect the implicit evaluation of goodness of others. Seventy-three women participated in the study. After the visuotactile multisensory stimulation procedure, participants were administered the Single Category Implicit Association Test (SC-IAT), which presents two attributes (good and bad) and one concept (other) was used. Results showed that the more attractive the faces are, the more positive their implicit evaluation becomes after the synchronous tactile stimulation. This result suggests that shared multisensory experience make people feel more positive towards others who have positive attribute. This finding suggests that self-other blurring in social contexts might be a compelling factor in evaluating other people positively.